Economic analysis of the adoption of Agro-Climatic Bulletin (ACB) at farm level in Tien Giang province - Alliance of Bioversity International and CIAT (2022)
This study aims to provide evidence of the adoption and benefits of climate service products for farmers’ rice production in Tien Giang province (MRD). ACBs were piloted in Tan Phuoc commune, Go Cong Dong district, Tien Giang province during Winter-Spring season 2020-2021. It was then replicated in all communes of Go Cong Dong district of Tien Giang during the Summer-Autumn rice season of 2021 and scaled across the province during the Winter-Spring season of 2021-2022 and the Summer-Autumn season of 2022. The study is not just limited to economic benefits at the farm level but also included other aspects project partners are interested in for policy advocacy such as changes in farmers’ behaviors and practices.